A4NH 2018 annual report - CGIAR Research Program on Agriculture for Nutrition and Health (International Food Policy Research Institute, 2019)
International agricultural research grapples not just with ensuring food security for the poor, but also with dynamic food systems, multiple burdens of malnutrition, and equity issues. Consumers are driving change, with demand for more diverse diets, greater convenience, and food safety assurances. Yet while markets are working to meet these needs in some areas, in others, they are not. Of greatest concern are those being left behind. The CGIAR Research Program on Agriculture for Nutrition and Health (A4NH) is a consortium of seven managing partners, led by IFPRI, working across five flagship research programs, addressing some of the most challenging nutrition and health concerns we face today. A4NH research concentrates on five focus countries, with work extending to more than two dozen others. Our research informs policymakers and stakeholders in those countries, and provides lessons adaptable to other places and contexts. This report highlights work conducted in 2018.